Dually Diagnosed: A Retrospective Study of the Process of Diagnosing Autism Spectrum Disorders in Children Who Are Deaf and Hard of Hearing - Szarkowski, Amy; Flynn, Suzanne; Clark, Terrell (Seminars in Speech and Language, 2014)
Utilizing a retrospective chart review of 30 children who have been dually diagnosed with hearing loss and autism spectrum disorders (ASDs), this study explores the process of arriving at the diagnosis of ASD in this population. Factors of interest include the age of ASD diagnosis in children who are deaf and hard of hearing, the types of professionals involved in making the diagnosis, and the measures used for assessment. Complications in the diagnostic process are highlighted.
Keywords: ASD; autism; deaf and hard of hearing; diagnosis; retrospective study